The clubroot pathogen Plasmodiophora brassicae: A profile update - Javed, Muhammad Asim; Schwelm, Arne; Zamani-Noor, Nazanin; Salih, Rasha; Silvestre Vañó, Marina; Wu, Jiaxu; González García, Melaine; Heick, Thies Marten; Luo, Chaoyu; Prakash, Priyavashini; Pérez‐López, Edel (Molecular Plant Pathology, 2023)
Background: Plasmodiophora brassicae is the causal agent of clubroot disease of cruciferous plants and one of the biggest threats to the rapeseed (Brassica napus) and brassica vegetable industry worldwide. Disease symptoms: In the advanced stages of clubroot disease wilting, stunting, yellowing, and redness are visible in the shoots. However, the typical symptoms of the disease are the presence of club-shaped galls in the roots of susceptible hosts that block the absorption of water and nutrients. Host range: Members of the family Brassicaceae are the primary host of the pathogen, although some members of the family, such as Bunias orientalis, Coronopus squamatus, and Raphanus sativus, have been identified as being consistently resistant to P. brassicae isolates with variable virulence profile. Taxonomy: Class: Phytomyxea; Order: Plasmodiophorales; Family: Plasmodiophoraceae; Genus: Plasmodiophora; Species: Plasmodiophora brassicae (Woronin, 1877). Distribution: Clubroot disease is spread worldwide, with reports from all continents except Antarctica. To date, clubroot disease has been reported in more than 80 countries. Pathotyping: Based on its virulence on different hosts, P. brassicae is classified into pathotypes or races. Five main pathotyping systems have been developed to understand the relationship between P. brassicae and its hosts. Nowadays, the Canadian clubroot differential is extensively used in Canada and has so far identified 36 different pathotypes based on the response of a set of 13 hosts. Effectors and resistance: After the identification and characterization of the clubroot pathogen SABATH-type methyltransferase PbBSMT, several other effectors have been characterized. However, no avirulence gene is known, hindering the functional characterization of the five intercellular nucleotide-binding (NB) site leucine-rich- repeat (LRR) receptors (NLRs) clubroot resistance genes validated to date. Important Link: Canola Council of Canada is constantly updating information about clubroot and P. ...